Characterizing the interactions between sediment dissolved organic matter and zinc using multispectroscopic techniques - Lü, Weiwei; Yao, Xin; Ren, Haoyu; Deng, Huanguang; Yao, Min; Zhang, Baohua (Environmental pollution (1987), 2020)
Sediment dissolved organic matter (DOM) was collected in November 2018 from Lake Dongping, China. The lake was divided into the entrance of the Dawen River, the open region of the lake, the tourism district and the macrophyte-dominated region based on principal component analysis (PCA) of 9 DOM-related parameters. Multispectroscopic tools were used to investigate the binding of zinc (Zn) with four kinds of DOM collected from the entrance of the Dawen River (EDOM), the open area of the lake (ODOM), the macrophyte-dominated area (mainly dominated by Potamogeton crispus L.) (PDOM) and the tourism district (TDOM). Three fluorescent components, the humic-like (components 1 and 3) and protein-like (component 2) components, were found by excitation-emission matrix spectra with parallel factor analysis. The EDOM, ODOM and TDOM were controlled by protein-like components, and the PDOM was controlled by humic-like components. Different components respond differently to Zn addition. The binding order of the tyrosine-like fraction > the tryptophan fraction > the humic-like fraction was identified by Synchronous fluorescence (SF) spectra and two-dimensional correlation spectroscopy (2D-COS). The fluorescence intensity of the protein-like component was suppressed, and the humic-like component was enhanced with the addition of Zn. The effective quenching constants (log K) of the protein-like component in PDOM were clearly higher than those in the EDOM, ODOM and TDOM, indicating higher metal binding potential in PDOM than in other kinds of DOM in Lake Dongping. The %Fmax (the amounts of each component measured as % of the total fluorescence maxima for the three components) of the humic-like components exhibited a gradual increase in all kinds of DOM with the addition of Zn, suggesting that the addition of Zn increased the humification of DOM. [Display omitted] •Different Zn-DOM binding affinities in different lake regions were investigated.•Lake Dongping was divided into four regions based on PCA.•Protein-like component was quenched and humic-like component was released with Zn addition.•The interaction of Zn with PDOM was stronger than with EDOM, ODOM and TDOM.